2017
DOI: 10.1002/mnfr.201700459
|View full text |Cite
|
Sign up to set email alerts
|

Appetite‐Inducing Effects of Homoeriodictyol: Two Randomized, Cross‐Over Interventions

Abstract: NaHED demonstrated appetizing effects in healthy adults when administered with a glucose load. Long-term intervention studies are warranted to verify these effects in compromised subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In our study, reduced serotonin plasma concentrations underline the higher intake of total energy from the standardized breakfast after receiving the sucrose + lactisole solution compared to sucrose application. Such an association between serotonin plasma levels and energy intake in men has been shown before [ 37 ]. In addition, the results of this study find support in recent in vitro findings that showed an increased serotonin release in human gastric parietal cell line after exposure to caloric or non-caloric sweeteners.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, reduced serotonin plasma concentrations underline the higher intake of total energy from the standardized breakfast after receiving the sucrose + lactisole solution compared to sucrose application. Such an association between serotonin plasma levels and energy intake in men has been shown before [ 37 ]. In addition, the results of this study find support in recent in vitro findings that showed an increased serotonin release in human gastric parietal cell line after exposure to caloric or non-caloric sweeteners.…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, ghrelin, glucagon‐like‐peptide1 (GLP‐1), PYY 3–36 , and serotonin concentrations were measured in the plasma as orexigenic and anorexigenic markers. The crossover study design in this short‐term intervention trial was conducted based on previous works which reported an impact of other aroma active food constituents on food intake and hormonal regulation of satiety …”
Section: Introductionmentioning
confidence: 99%
“…The crossover study design in this short-term interven-tion trial was conducted based on previous works which reported an impact of other aroma active food constituents on food intake and hormonal regulation of satiety. [32,33]…”
Section: Introductionmentioning
confidence: 99%
“…In multiple studies that recorded the outcomes over several hours on just one or two days, respectively, participants were instructed to refrain from exercise 24 to 48 h before test day [28,51,60,61,62,65,75] and to arrive after an overnight fast at the test center [52,57,62,69,70,76,86]. The bioactive phytochemical was mostly taken with a standardized meal, varying from a breakfast meal with approximately 1150 kJ (275 kcal) [73] to a breakfast buffet with a total amount of approximately 32,962 kJ (7878 kcal) [61].…”
Section: Resultsmentioning
confidence: 99%